Diplomasi Kebudayaan Korea Selatan di Indonesia Melalui Komunitas Sahabat Korea Tahun 2019-2021 - Zulfian, Muhammad Haekal (Universitas 17 Agustus 1945 Jakarta, 2024)
This journal explores South Korean cultural diplomacy in Indonesia during the years 2019-2021, focusing on the role played by the